Closed-loop optimization control on fan speed of air-cooled steam condenser units for energy saving and rapid load regulation. (15th September 2017) - Yang, Tingting; Wang, Wei; Zeng, Deliang; Liu, Jizhen; Cui, Can
Abstract: In order to save more energy and quicken the load change speed of air-cooled steam condenser units, the closed-loop optimized control on the fan speed is proposed and its realization is worth making intensive study. In this regard, the study presents the static and dynamic models of air-cooled steam condenser, and the characteristics of turbine power output affected by fan speed. Then, the structure of closed-loop control on fan speed is designed. Furthermore, two optimized methods on condenser pressure based on fan speed control are separately discussed: the optimum condenser pressure is solved by the genetic algorithm to save more energy, and the condenser pressure regulation is combined with traditional boiler-turbine coordinated control to accelerate the load response. Case study in our paper proves that the fan speed optimization can significantly improve the unit load-following capability, and furthermore unit coal consumption has been significantly reduced when the unit operating in a stable load condition. Highlights: The static and dynamic models of fan speed on turbine load are set up. The closed-loop optimization control strategy on fan speed is designed. The description and solution for optimum condenser pressure is presented. A load-change method combined CCS and condenser pressure regulation is proposed. Our strategy is proved to be effective on energy saving and rapid load regulation.